Crystal growth, surface morphology, mechanical and thermal properties of UV-nonlinear optical crystal: Mercury cadmium chloride thiocyanate (MCCTC) single crystal. Issue 1 (June 2020) - Ramesh, V; Gunasekaran, B; Suresh, P; Sundaravadivel, E; Showrilu, K; Rajarajan, K
Abstract: Single crystal of mercury cadmium chloride thiocyanate (MCCTC) was grown by slow evaporation solvent method at ambient temperature (SEST) with a dimension of 10×5×5 mm 3 . The grown single-crystal's structure and lattice constant, density and volume were estimated by using single-crystal X-ray diffraction studies. Additionally, the chemical etching and atomic force microscopy (AFM) analysis were used to investigate reverse growth and surface morphology. Moreover, the mechanical properties such as, hardness number, yield strength, Mayer index number, and stiffness constant were calculated by Vickers's micro-hardness measurement. The thermal stability of grown single is stable up to 171 °C observed from TG-DSC, which reveals that the sample posses low thermal stability compared to other organometallic thiocyanate families of single crystals like MMTC(381°C), MFCTC (241°C) and ACCTC (247 °C). The non-linear optical study of second harmonic generation efficiency for MCCTC single crystal is 17 times superior to Urea.